In vivo implant fixation of carbon fiber‐reinforced PEEK hip prostheses in an ovine model. Issue 3 (23rd October 2012) - Nakahara, Ichiro; Takao, Masaki; Bandoh, Shunichi; Bertollo, Nicky; Walsh, William R; Sugano, Nobuhiko
Abstract Carbon fiber‐reinforced polyetheretherketone (CFR/PEEK) is theoretically suitable as a material for use in hip prostheses, offering excellent biocompatibility, mechanical properties, and the absence of metal ions. To evaluate in vivo fixation methods of CFR/PEEK hip prostheses in bone, we examined radiographic and histological results for cementless or cemented CFR/PEEK hip prostheses in an ovine model with implantation up to 52 weeks. CFR/PEEK cups and stems with rough‐textured surfaces plus hydroxyapatite (HA) coatings for cementless fixation and CFR/PEEK cups and stems without HA coating for cement fixation were manufactured based on ovine computed tomography (CT) data. Unilateral total hip arthroplasty was performed using cementless or cemented CFR/PEEK hip prostheses. Five cementless cups and stems and six cemented cups and stems were evaluated. On the femoral side, all cementless stems demonstrated bony ongrowth fixation and all cemented stems demonstrated stable fixation without any gaps at both the bone‐cement and cement‐stem interfaces. All cementless cases and four of the six cemented cases showed minimal stress shielding. On the acetabular side, two of the five cementless cups demonstrated bony ongrowth fixation. Our results suggest that both cementless and cemented CFR/PEEK stems work well for fixation. Cup fixation may be difficult for both cementless and cemented types in this ovine model, but bone ongrowth fixation on the cup was first seen in two cementless cases. Cementless fixation can be achieved using HA‐coated CFR/PEEK implants, even under load‐bearing conditions. © 2012 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 31: 485–492, 2013